Intraoperative glove perforation—singleversus double gloving in protection against skin contamination. Issue 909 (1st July 2001) - Thomas, S; Agarwal, M; Mehta, G
Abstract : Surgeons have the highest risk of contact with patients' blood and body fluids, and breaches in gloving material may expose operating room staff to risk of infections. This prospective randomised study was done to assess the effectiveness of the practice of double gloving compared with single gloving in decreasing finger contamination during surgery. In 66 consecutive surgical procedures studied, preoperative skin abrasions were detected on the hands of 17.4% of the surgeons. In the double gloving pattern, 32 glove perforations were observed, of which 22 were in the outer glove and 10 in the inner glove. Only four outer glove perforations had matching inner glove perforations, thus indicating that in 82% of cases when the outer glove is perforated the inner glove will protect the surgeon's hand from contamination. The presence of visible skin contamination was also higher in perforation with the single gloving pattern (42.1%) than with the double gloving pattern (22.7%). An overwhelming majority of glove perforations (83.3%) went unnoticed. Double gloving was accepted by the majority of surgeons, especially with repeated use. It is recommended that double gloves are used routinely in all surgical procedures in view of the significantly higher protection it provides.